Use of l-pNIPAM hydrogel as a 3D-scaffold for intestinal crypts and stem cell tissue engineering. (14th August 2019) - Dosh, Rasha H.; Jordan-Mahy, Nicola; Sammon, Christopher; Le Maitre, Christine L.
Abstract : Intestinal stem cells hold great potential in tissue regeneration of the intestine, however, there are key limitations in their culture in vitro . Abstract : Intestinal stem cells hold great potential in tissue regeneration of the intestine, however, there are key limitations in their culture in vitro . We previously reported a novel synthetic non-biodegradable hydrogel as a 3D culture model for intestinal epithelium using Caco2 and HT29-MTX cells. Here, we investigated the potential of this system as a 3D scaffold for crypts and single intestinal stem cells to support long-term culture and differentiation. Intestinal crypts were extracted from murine small intestines and Lgr5 + stem cells isolated by magnetic activated cell sorting. Crypts and stem cells were suspended within Matrigel orl -pNIPAM for 14 days or suspended within Matrigel for 7 days then released, dissociated, and suspended within, or onl -pNIPAM hydrogel for 28 days. Cellular behaviour and phenotype were determined by histology and immunohistochemistry for stem cell and differentiation markers: Lgr5, E-cadherin MUC2 chromograninA and lysozymes. Isolated crypts and Lgr5 + intestinal stem cells formed enteroids with a central lumen surrounded by multiple crypt-like buds when cultured in Matrigel. In contrast, when crypts and stem cells were directly suspended within, or layered onl -pNIPAM hydrogel under dynamic culture conditions they formed spherical balls of cells, with no central lumen. When enteroids were initially formed in Matrigel from crypts or single Lgr5 + intestinal stem cells and dissociated into small fragments or single cells and transferred tol -pNIPAM hydrogel they formed new larger enteroids with numerous crypt-like buds. These crypt-like buds showed the presence of mucin-producing cells, which resembled goblet cells, scattered throughout their structures. Immunohistochemistry staining also showed the expression of Lgr5 and differentiation markers of all the main intestinal cell types including: enterocytes, goblet cells, enteroendocrine and Paneth cells. This demonstrated thatl -pNIPAM hydrogel supported long-term culture of crypts and Lgr5 + stem cells and promoted intestinal cell differentiation.